2017
DOI: 10.21608/ajas.2017.7572
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Purification of Alkaline Proteases From Viscera of Silver Carp (Hypophthalmichthys molitrix) Fish

Abstract: Proteases from viscera of Silver carp (Hypophthalmichthys molitrix) fish have been extracted and characterized. The alkaline proteases show optimum activity in 0.2M Tris-HCl buffer at pH 8.5 and 45°C using soluble milk casein as substrate. The crude alkaline protease lost about 35% or 51% of its specific activity if it was heated at 50C or kept at pH 9 for 60 min., respectively. Purification of proteases purified by ammonium sulfate precipitation, gel-filtration using Sephadex G 50 column and ultrafiltration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The results presented in Table 2 revealed the highest EA at pH of 8 and temperature of 50°C. Previous studies also indicated that enzymes extracted from marine and fisheries substance with neutral buffers tend to have optimum EA at alkaline condition (pH of 8-9) and temperature range 45-60°C [3,18,19]. Vannabun et al (2014) reported higher EA of alkaline protease enzyme extracted from giant catfish viscera compared to acid protease [20].…”
Section: Enzyme Activity Of Crude Enzymementioning
confidence: 91%
“…The results presented in Table 2 revealed the highest EA at pH of 8 and temperature of 50°C. Previous studies also indicated that enzymes extracted from marine and fisheries substance with neutral buffers tend to have optimum EA at alkaline condition (pH of 8-9) and temperature range 45-60°C [3,18,19]. Vannabun et al (2014) reported higher EA of alkaline protease enzyme extracted from giant catfish viscera compared to acid protease [20].…”
Section: Enzyme Activity Of Crude Enzymementioning
confidence: 91%
“…Proteases are the most widely used group of enzymes in industrial bioprocesses, which is why they represent about 40%-65% of the total commercial enzyme preparations (Atta et al, 2017). In this sense, fish viscera are one of the most important wastes because they contain digestive enzymes, especially aspartic proteinases (pepsin) in the stomach and serine proteinases (trypsin, chymotrypsin, collagenase and elastase) in the intestine and pyloric ceca (Klomklao et al, 2011;Vannabun et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Proteases are the most widely used group of enzymes in industrial bioprocesses so they represent about 40-65% of the total commercial enzyme preparations (Atta et al 2017). In this sense, sh viscera are one of the most important wastes because they contain digestive enzymes, especially aspartic proteases (pepsin) in stomach, and serine proteases (trypsin, chymotrypsin, collagenase, and elastase) in intestine and pyloric ceca (Klomklao et al 2011;Vannabun et al 2014;Välimaa et al 2019).…”
Section: Introductionmentioning
confidence: 99%